The Role of the Sabhara Four-Wheel Motorized Vehicle Patrol Unit in Suppressing the Crime of Theft of Two-Wheeled Motorized Vehicles at the Purwakarta Police - Firoos Salsabiil, Marco (Indonesian Journal of Police Studies, 2024)
The crime of two-wheeled carnage at Purwakarta Police has the highest number and has increased over the past three years. The preventive role of four-wheeled motor vehicle patrols has not been maximized. This study aims to determine the general description of two-wheeled curanmor in Purwakarta Regency, the role of four-wheeled motorized patrol units in suppressing two-wheeled carnage crime, and the influencing factors. Theories used in this research are routine activity theory, management theory, and 6M theory. The concepts used are the concept of roles, the concept of fraud, the concept of Sabhara, the concept of four-wheeled patrol, and the concept of crime prevention. This study uses a qualitative approach with field research methods. Data sources used are primary data sources and secondary data sources. Data collection techniques used were interviews, observation and document study. And data analysis used is data reduction, data presentation, and drawing conclusions. The results found that the two-wheeled churn was found to be the most using the lock T mode, type of Honda Beat motorbike, home page crime scene, time pattern 03.00 - 05.00 and the monotone map of vulnerability analyzed with routine activity theory. The role of four-wheeled patrol has a monotonous route, there was no AAP before patrolling, officers were negligent in patrolling, and the lack of supervision from the leadership was analyzed by management theory. The inhibiting factors were that many officers did not match their competence, the budget was inadequate, the message of the Kamtibmas was not well prepared, vehicle damage, dialogic patrol methods, and lack of support from the community were analyzed with the 6M theory. The conclusion of the implementation of four-wheeled patrol still has no role in suppressing the two-wheeled vehicle. The advice given is to strengthen the synergy of the community and patrol officers, normative four-wheeled patrol in accordance with Perkabahrkam No. 1 of 2017, and fix patrol inhibiting factors.